Pembuatan Aplikasi Sistem Informasi Akuntansi pada Toko JB di Mataram - Andri Hermawan Sukasto; Alexander Setiawan; Silvia Rostianingsih (Jurnal Infra, 2017)
JB stores in Mataram was a business line engaged in sales materials and tools of building work related. Materials and tools that JB sale includes cement, iron, nails, hammers, cat, lay pipes and so on. The business process of JB stores, all the record is done by user from operating from sales, purchasing, and book keeping. However, for a review stock items only partially record.Seeing their information system related the problems that can be computerized accounting and improve business process control on store building in Mataram. The Accounting Information Systems is created using PHP programming language support with yii framework and MySQL database. The application is generated from application between recording of the parent to review customers, suppliers, categories of goods, goods, COA, and the book is big, addition that registration of transactions include purchases and sales, as well as the Financial Statements form of purchase report, sales report, income statement, total owner, and balance.Application has overall operational according with building supplies stores in Mataram. From the findings of the questionnaire what do note that 100% of users think the design program is considered good, as well as completeness of information needed rated good, 60% of users believe Regarding the accuracy of the information and data that are considered good, 60% of users think the good about benefits applications and operating entirety applications rated good by 100% of users.